Use of rare-earth elements to achieve wavelength-selective absorption in high-power fibre lasers. (September 2018) - Kochergina, T.A.; Aleshkina, S.S.; Khudyakov, M.M.; Yashkov, M.V.; Lipatov, D.S.; Abramov, A.N.; Iskhakova, L.D.; Bubnov, M.M.; Gur'yanov, A.N.; Likhachev, M.E.
Abstract: We have studied absorption spectra of optical fibres doped with rare-earth ions (Sm 3+, Tm 3+, Tb 3+, Pr 3+ and Ho 3+ ) and demonstrated that they are potentially attractive for ensuring wavelength-selective absorption in fibre lasers. Such fibres can be used for pump diode protection against back-reflected light at the operating wavelength of neodymium, erbium, erbium – ytterbium or thulium lasers. A proper choice of a rare-earth element makes it possible to ensure a strong absorption (10 – 20 dB) at the operating laser wavelength in combination with high transmission (loss under a few tenths of a decibel) at pump wavelengths. To demonstrate the potential of the proposed approach, we have fabricated and investigated Tm 3+ -doped fibre compatible with the output fibre pigtails of standard semiconductor diodes used for pumping (core diameter, 105 μm; numerical aperture, 0.22). We have demonstrated the possibility of effectively suppressing light in the 1550-nm range by more than 20 dB even in the case of a high-power (up to 10 W) undesirable signal. Under such conditions, the total pump loss does not exceed 0.5 dB and can be further reduced by optimising the core composition and fibre design.